Mapping Quantitative Trait Loci Affecting Biochemical and Morphological Fruit Properties in Eggplant (Solanum melongena L.) - Toppino, Laura; Barchi, Lorenzo; Lo Scalzo, Roberto; Palazzolo, Eristanna; Francese, Gianluca; Fibiani, Marta; D'Alessandro, Antonietta; Papa, Vincenza; Laudicina, Vito A.; Sabatino, Leo; Pulcini, Laura; Sala, Tea; et al. (Frontiers in Plant Science, 2016)
Eggplant berries are a source of health-promoting metabolites including antioxidant and nutraceutical compounds, mainly anthocyanins and chlorogenic acid; however, they also contain some anti-nutritional compounds such as steroidal glycoalkaloids (SGA) and saponins, which are responsible for the bitter taste of the flesh and with potential toxic effects on humans. Up to now, Quantitative Trait Loci (QTL) for the metabolic content are far from being characterized in eggplant, thus hampering the application of breeding programs aimed at improving its fruit quality. Here we report on the identification of some QTL for the fruit metabolic content in an F2 intraspecific mapping population of 156 individuals, obtained by crossing the eggplant breeding lines ‘305E40’ x ‘67/3’. The same population was previously employed for the development of a RAD-tag based linkage map and the identification of QTL associated to morphological and physiological traits. The mapping population was biochemically characterized for both fruit basic qualitative data, like dry matter, °Brix, sugars and organic acids, as well as for health-related compounds such chlorogenic acid, (the main flesh monomeric phenol), the two peel anthocyanins (i.e. delphinidin-3-rutinoside (D3R) and delphinidin-3-(p-coumaroylrutinoside)-5-glucoside (nasunin)) and the two main steroidal glycoalkaloids, solasonine and solamargine. For most of the traits, one major QTL (PVE ≥ 10%) was spotted and putative orthologies with other Solanaceae crops are discussed. The present results supply valuable information to eggplant breeders on the inheritance of key fruit quality traits, thus providing potential tools to assist future breeding programs.